Indoor Air Quality Assessment For A Multistorey University Office Building In Malaysia - Abdullah, A.H.; Lee, Yee Yong; Aminudin, E.; Lee, Y.H. (College Publishing, 2019)
The indoor air quality (IAQ) in office buildings should be assessed for public health concerns as it relates to work performance and productivity. Therefore, this paper aims to assess the IAQ in a university office building. From this investigation, the level of contaminated indoor air is examined, the significant causes and contributing factors of contaminated indoor air are determined and a recommendation to improve the existing condition has been proposed. The physical parameters measured include air temperature, air velocity, relative humidity, and concentrations of carbon dioxide (CO2), carbon monoxide (CO), sulphur dioxide (SO2), and also air particles. It was found that the number of air particles of 0.5 μm in diameter is about 197,748 particles/m3 , while air particles of 5.0 μm in diameter is around 534 particles/m3 . The collected data were then compared with a questionnaire and IAQ standards. In conclusion, the indoor air quality within the multi-storey central office building of Universiti Tun Hussein Onn Malaysia (UTHM) is acceptable and suitable for occupation even though there were countable symptoms of Sick Building Syndrome (SBS) among its occupants.